Adherence of staphylococcus aureus to influenza A virus-infected Madin-Darby canine kidney cell cultures. - Davison, V E (1981)
Madin-Darby canine kidney cells infected with influenza A virus (strains PR8, FM1, Jap 305, and Tex 1) were tested with nine strains of Staphylococcus aureus and group B Streptococcus type Ic to determine whether mammalian cells become susceptible to bacterial adherence as a result of virus infection. Bacterial adherence to virus-infected cells varied depending on the virus strain and on the strain of bacteria tested. A quantitative radioassay was developed to study the parameters of adherence. Attachment of 3H-labeled S. aureus grown in chemically defined or biologically complex medium to FM1 virus-infected cells was significantly increased (P less than 0.0005) compared with attachment to control cells. Adherence coincided with the appearance of hemadsorption, which is a marker of the presence of virus-induced glycoproteins on the cell surface. Adherence was temperature dependent, increased with a decrease in hydrogen ion concentration, and was not affected by the presence of K+, Mg2+, or Ca2+. Adherence was blocked when 3H-labeled S. aureus was pretreated with trypsin but not when cells were pretreated with neuraminidase.